Hubungan Pengetahuan Gizi dan Perilaku Higiene Sanitasi Terhadap Kejadian Stunted pada Balita Usia 7-24 Bulan di Desa Hargorejo Kulon Progo - Oktaviana, Herni, Dwi Sarbini, SST, Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Stunted is a linear growth delay. Stunted often related to the nutrition and the health in condition during pregnancy, lactation, a newborn and children under two. Among mothers are two of the factors which can cause stunted, lack of nutrition knowledge and bad higiene sanitation behavior. Mothers' knowledge about nutrition would affect food intake of children, while mothers' higiene sanitation behavior relate to incidence infection in children. To determine the relationship of mothers' knowledge about nutrition and higiene sanitation behavior with the incidence of stunted in toddlers age 7-24 months in Hargorejo Village, Kulon Progo Regency, Special Region of Yogyakarta. Observational research with cross-sectional design using 47 respondents who were obtained by the systematic random sampling technique. Mothers' knowledge of nutrition and higiene sanitation behavior data were obtained through the interview using a questionnaire. To analyze the data, Pearson statistical test was used. Most of mothers' knowledge about nutrition was categorized as good (61,7%) and most of mothers' behavior on higiene sanitation was categorized as good (80,9%), while 46,8% of the respondent were stunted. Mother with low knowledge about nutrition have lower stunted toddler (44,4%) compared to that of with good knowledge about nutrition (48,3%). Mother with middle higiene sanitation behavior have lower stunted toddler (44,4%) compared to that of with good higiene sanitation (47,4%). Based on the Pearson statistical test, if there is a relationship between mothers' higiene sanitation behavior with the incidence of stunted (ρ=0,017) and there is no relationship between mothers' knowledge about nutrition with the incidence of stunted (ρ = 0,238). There is a relationship between mothers' higiene sanitation behavior with the incidence of stunted and there is no relationship between mothers' knowledge about nutrition with the incidence of stunted.